The effect of decalcified bone matrix on the osteogenic potential of bone marrow. - Green, E; Hinton, C; Triffitt, J (1986)
Rabbit bone marrow cells were cultured in diffusion chambers with or without decalcified bone matrix. The chambers were assayed after 28 days for alkaline phosphatase activity, deoxyribonucleic acid (DNA), calcium, and phosphorus contents. Morphologically, marrow cells incubated with or without matrix differentiated to form bone and cartilage. With bone matrix, the calcium and phosphorus contents of chambers were significantly higher than control chambers. Alkaline phosphatase activity and DNA content were not influenced by inclusion of bone matrix. These results indicate that bone matrix constituents exert a stimulatory effect on bone formation from marrow cells. This osteogenic stimulation could be due to the influence of an osteoinductive factor and/or to stimulation of osteoprogenitor cells known to be present in the marrow.